PROTECTIVE EFFECT OF A PHYLLANTHUS EMBLICA EXTRACT AGAINST CISPLATIN-INDUCED APOPTOSIS IN DERMAL PAPILLA FIBROBLASTS - Luanpitpong, S.; Nimmannit, U.; Pongrakhananon, V.; Chanvorachote, P. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Cisplatin is a widely prescribed anticancer agent that causes hair loss in patients. Since the dermal papilla (DP) fibroblasts are known as a key mediator in controlling hair growth and loss, protection against cisplatin-induced cell damage on these cells may lead to a new strategy for hair loss protection in chemotherapy patients. We herein reported that cisplatin induced DP cell death in a concentration-dependent manner through apoptosis mechanism, which was further found to be related to the intracellular reactive oxygen species (ROS) generation. Therefore, extract from emblica fruits (Phyllanthus emblica), a known natural antioxidant, was examined for its protective effect on cisplatin-induced DP fibroblast cell death. Our results indicated that emblica extract attenuated the intracellular ROS induction following cisplatin treatment and subsequently protected against cisplatin-induced DP fibroblast apoptotic cell death. Co-treatment of emblica extract (250-500 µg/mL) and cisplatin 100 µmol/L (LD50) markedly increased the DP fibroblast relative cell viability to the same level as the non-treated control.